Dynamic compression plate (DCP) fixation of propagating medial condylar fractures of the third metacarpal/metatarsal bone in 30 racehorses: Retrospective analysis (1990–2005). (7th January 2014) - Goodrich, L. R.; Nixon, A. J.; Conway, J. D.; Morley, P. S.; Bladon, B. M.; Hogan, P. M.
Summary: Reasons for performing study: An in‐depth review of dynamic compression plate (DCP) fixation of propagating medial condyle fractures of the third metacarpus or metatarsus has not been previously reported. Objectives: To describe the technique, evaluate short‐term outcome and long‐term race performance of racehorses that underwent DCP fixation for repair of propagating or spiralling medial condylar fractures of the third metacarpal (McIII) or metatarsal (MtIII) bone. Study design: Retrospective case series. Methods: The surgical case records of 30 horses with propagating fractures of the medial condyle of McIII or MtIII were reviewed. Medical information included: age, breed, sex, presentation, how injury occurred (racing or training), surgical treatment and post operative complications. Racing information included: starts, top 3 placing and career earnings. Results: Long propagating fractures of the medial condyle of Mc/tIII were identified in 23 Thoroughbred (TB) and 7 Standardbred (STB) racehorses. The fracture spiralled proximally in 22 of 30 cases (73%). Standardbreds had a higher propensity for hindlimb involvement (71%), whereas TBs tended to have more front limb involvement (61%). Twelve of 30 (40%) horses raced post surgery. Career earnings were significantly lower for TB horses with medial condylar fractures; $34, 916 when compared with the national average of $60, 841 (P≤0.03). Overall, horses having DCP fixation for medial condylar fractures had less starts post surgery (3.1 TBs and 5.8 STBs) compared with the national average (7 TBs and 17.3 STBs) and decreased lifetime starts 13.4 (TBs) compared with 17.3 nationally. Conclusions: Propagating medial condyle fractures can be repaired with plate fixation to potentially lessen the risk of catastrophic fracture destabilisation and return to racing can be expected in 40% of horses. Further prospective studies are warranted comparing lag screw fixation with DCP fixation for repair of severe medial condylar fractures of the metacarpus/metatarsus.